2021
DOI: 10.1111/jace.17863
|View full text |Cite
|
Sign up to set email alerts
|

Cold sintering of diatomaceous earth

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 63 publications
(128 reference statements)
0
9
0
2
Order By: Relevance
“…During the CSP, when suitable liquid aids are selected to dissolve the edges of the particles, the pores between the particles can be eliminated by the evaporation of the solvent and precipitation of the solute [17,18]. So far, many oxide materials including ZrO 2 [19], MgO [20], Bi 2 O 3 [21], CaCO 3 [22], and SiO 2 [23][24][25][26][27], have been successfully prepared by the CSP. However, very few studies related to the CSP-densified glass materials have been demonstrated [28].…”
mentioning
confidence: 99%
“…During the CSP, when suitable liquid aids are selected to dissolve the edges of the particles, the pores between the particles can be eliminated by the evaporation of the solvent and precipitation of the solute [17,18]. So far, many oxide materials including ZrO 2 [19], MgO [20], Bi 2 O 3 [21], CaCO 3 [22], and SiO 2 [23][24][25][26][27], have been successfully prepared by the CSP. However, very few studies related to the CSP-densified glass materials have been demonstrated [28].…”
mentioning
confidence: 99%
“…The process shares an analogy to a combination of hot pressing and liquid-assisted sintering. [144] During the cold sintering process, a capillary force is formed under the applied uniaxial pressure, and the ratio between the concentration of the transient liquid and the corresponding pressure affects the particle rearrangement, dissolution, and precipitation and hence, the possible grain growth and densification. [147] The detailed cold sintering process can be understood in two stages.…”
Section: Cold Sinteringmentioning
confidence: 99%
“…Os componentes adicionados têm o papel de garantir que no segundo estágio do processo a composição formada do material depositado devido a evaporação da fase líquida seja similar a composição da matriz cerâmica já consolidada (WANG, 2020). De acordo com Galotta et al (2021), os primeiros materiais feitos por CSP foram principalmente sais e compostos solúveis, mas também foram produzidos materiais ferroelétricos, piezoelétricos, cerâmica magnética, semicondutores, biocerâmicas e condutores iônicos (GALOTTA, 2021). Assim verifica-se um grande rol de cerâmicas que podem ser produzidas pela técnica de CSP, abrangendo um amplo campo de atuação para materiais cerâmicos.…”
Section: Características Dos Processos De Sinterização a Friounclassified
“…O volume de poros e área superficial são parâmetros importantes na compreensão da morfologia interna das cerâmicas e poderão ser avaliados pelos métodos de Adsorção/Dessorção de Nitrogênio e Brunauer-Emmett-Teller (BET). Outras técnicas de espectroscopia poderão ser usadas em casos específicos (GALOTTA, 2021;GIRALDI, 2012;HASHMI, 2016;INDUJA, 2017;NDAYISHIMIYE, 2020;ZAHABI, 2021). Ensaios de caracterização mecânica, térmica e elétrica são também realizados de acordo com as características dos produtos de cada trabalho.…”
Section: Caracterização Dos Produtosunclassified